Monetary Poverty in Inuit Nunangat - Duhaime, Gérard; Édouard, Roberson (ARCTIC, 2015)
This article measures for the first time the scope of poverty in Inuit Nunangat, the four regions of the Canadian Arctic where Inuit people live. On the basis of a monetary definition of poverty, we propose and apply a method adapted to key characteristics of the Inuit condition. For each region, we developed a low income measure (LIM) that takes household composition and consumer prices into account, using data from the master file of the 2006 Census of Canada and surveys by Aboriginal Affairs and Northern Development Canada on the Revised Northern Food Basket. For Inuit Nunangat as a whole, the low income measure was $22 216 and the low income rate (LIR) was 44%. Values vary among regions: in Nunavik, for example, the low income rate is 37.5%. However, throughout Inuit Nunangat, poverty rates are significantly higher than those observed in Canada. We recommend further statistical exploration to better identify not only the factors correlated with households living in poverty, but also a qualitative approach to produce an Inuit emic perspective. Both tools are necessary for informed policy to fight against poverty. Cet article mesure, pour la première fois, l’étendue de la pauvreté dans l’Inuit Nunangat, les quatre régions de l’Arctique canadien habitées par les Inuits. En nous fondant sur une définition monétaire de la pauvreté, nous proposons une méthode qui tient compte de caractéristiques de la condition inuite : pour chacune des régions, nous avons développé une mesure du faible revenu (MFR) qui reflète la composition des ménages par l’utilisation des données du fichier-maître du Recensement du Canada de 2006, et les prix à la consommation par l’utilisation des données du Panier de provision nordique révisé calculé par le ministère des Affaires autochtones et du Développement du Nord du Canada. Pour l’ensemble de l’Inuit Nunangat, la mesure du faible revenu (MFR) obtenue se situait à 22 216 $, et le taux de faible revenu (TFR) était de 44 %. Les résultats varient selon les régions : au Nunavik, par ...